The Map of Britain in British Library, MS Harley 1808. Issue Volume 74:Issues 2(2022) (3rd July 2022) - Hiatt, Alfred
ABSTRACT: This article provides a detailed description and analysis of the map of Britain in British Library, MS Harley 1808, in its manuscript context and in comparison with the Gough map of Britain. It is argued that the map in MS Harley 1808, which can be dated to between 1422 and c .1450, was almost certainly copied in York. Detailed consideration of it in its manuscript context shows that it could be read as a support to the narrative of British history which traced the lineage of English kings back to the legendary founder of the kingdom, Brutus. Concluding remarks consider the implications of that reading for the Gough map. An appendix lists toponyms on the map of Britain in MS Harley 1808 and compares them with their equivalents on the Gough map.